COMPARISON OF DERIVATIZATION AND SOLID-PHASE MICROEXTRACTION OF A SET OF AROMATIC ALDEHYDES AND DIALDEHYDES FOR GC/FID DETERMINATION IN AQUEOUS SAMPLES: DOI: https://doi.org/10.17721/1728-2209.2024.1(59).3 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. One of the main advantages of chromatography is the ability to separate and simultaneously determine a large number of compounds. In the case of the analysis of aldehydes, in addition to the optimization of chromatographic separation and detection, methods are designed to include sample preparation and derivatization with the selection of optimal conditions. Among the methods available in the literature, there are some that enable the determination ranging from a few to 80 or more carbonyl compounds simultaneously, with varying sensitivity. The aim of this work was to investigate the differences in derivatization using O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine and in the solid-phase microextraction of a number of aromatic aldehydes and dialdehydes during determination using gas chromatography.Methods. The methods of solid-phase microextraction and gas chromatography (with a flame ionization detector) were used in this work. For measurements that required avoiding the possible impact of solid-phase extraction conditions on the results, liquid extraction with hexane was used.Results. The study has shown that derivatization parameters such as pH and reaction time differ slightly for aromatic aldehydes and dialdehydes, while the effect of ionic strength during solid-phase microextraction can lead to both an increase as well as a decrease in the analytical signal depending on the structure (nature) of the aldehyde and its derivative. The histograms and graphical dependences of the peak areas of analytes on the parameters of derivatization and solid-phase microextraction presented in this paper illustrate the effect of different sample preparation conditions on the analytical signal of aldehydes and, therefore, on the sensitivity of the determination.Conclusions. In this work, the effect of parameters of derivatization and solid-phase microextraction of aldehydes of different nature, aromatic and dialdehydes, on gas chromatography with flame ionization detection determination was investigated. It was found that the optimum temperature for solid-phase microextraction for most aldehydes is 80 ℃, for 2-furaldehyde the analytical signal decreases by 30 % from the maximum when the temperature increases from 50 to 80 ℃, and the transition from 1 to 10 % sodium chloride content in aqueous solution reduces the analytical signal by 40 % for dialdehydes. Considering the above, a significant loss in sensitivity is observed for some of the aldehydes studied in the determination of a mixture of aldehydes. Therefore, when determining the analytes, it is necessary to differentiate the conditions of derivatization and solid-phase microextraction of aromatic aldehydes and dialdehydes, and sample preparation of samples containing 2-furaldehyde should be carried out individually under different conditions.
Keywords: solid-phase microextraction; sample preparation; gas chromatography; derivatization; sorption